The quality of service and user satisfaction of airline chatbots - Arreza, Mariae Khrisna Baring (Journal of Business on Hospitality and Tourism, 2022)
Chatbots have shown to be a viable alternative to customer service agents in addressing customer questions and concerns. The airline sector has developed chatbots to meet the needs of their customers. In this paper, the study presents findings from a questionnaire involving 417 chatbot users. The assessment revealed that the quality of the airline chatbot service was deemed good, and users were satisfied with the airline chatbot service. This study also tested the relationship between the variables of the study. The outcomes revealed a significant relationship between users' profiles and the quality of the service provided by the chatbot. A significant relationship manifested between the users' profile and their satisfaction with the airline chatbot service. The results also discover a highly significant relationship between the quality of airline chatbot service and the users' satisfaction. Drawing on the findings, Developers should enhance chatbots to provide better service and boost customer satisfaction.